Penyelesaian Perselisihan Hubungan Industrial antara Pekerja dengan PT Suzuki Finance Indonesia pada Tingkat Mediasi di Dinas Tenaga Kerja, Koperasi dan UKM Kabupaten Banyumas - Rosita Candrakirana; Nadia Sekarsari; Rahayu Subekti (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
This research intend to determine and resolve the process of dispute settlement of industrial relations between employee and PT Suzuki Finance Indonesia Branch Office Purwokerto on mediation step that was held at Dinas Tenaga Kerja, Koperasi dan UKM Kab. Banyumas. This research using normative and empirical methods which use primary and secondary legal materials. Also using interview data sources with the mediator of Dinnakerkop UKM Kab. Banyumas and documentary study. The conclusion of this research is the dispute settlement of industrial relations on this case already in accordance with PPHI Law, but there are obstacles that cause the solution of industrial relation can not to be done in the mediation step.